Pengaruh Motivasi dan Kompetensi Guru terhadap Kinerja Guru SD Negeri 5 Banda Sakti Lhokseumawe - Ramlan, Ramlan (PAI Fakultas Tarbiyah & Ilmu Keguruan UIN SUNA Lhokseumawe, 2024)
This study aims to determine the partial effects of (1) motivation on teacher performance, (2) competence on teacher performance, and (3) the combined effect of motivation and competence on teacher performance. The research was conducted at SD Negeri 5 Banda Sakti using a quantitative method, with data processing techniques multiple regression analysis. The sample was collected using the total sampling technique, with the entire population of 30 teachers included in the sample. Data was gathered using a Likert-scale questionnaire. The findings showed that, partially, (1) the direct effect of motivation on teacher performance was 27.4; and (2) the direct effect of competence on teacher performance was 22.0. Simultaneously, the combined effect of motivation and competence on teacher performance was 43.50, while the remainder was influenced by other factors not examined in this study. The research recommends that synergy between motivation and competence should be fostered through comprehensive development programs, while teacher welfare must also be addressed to maintain their commitment. Regular performance evaluations are necessary to identify further development needs, and additional research is suggested to explore other factors affecting teacher performance.